Peningkatan Maharatul Kitabah Melalui Struktur Analisis Sintesis (Sas) Pada Pembelajaran Bahasa Arab Di Pondok Pesantren - Mu'allim Wijaya; Lailil Muharromah (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2018)
This paper presented about development of writing skill (maharotul kitabah) Through Analytic synthesis structure to Arabic studying in Islamic Boarding school of Nurul Jadid Paiton Probolinggo. In Arabic studying, writing skill (maharoh kitabah) is one of skill which can’t be ignored because writing has corelation with the process of expression skill. To write is one of communication that is not limited by time and place. In speaking context, the audience can be limited by certain place and time, but in writing, it can reach many people in differrent time and place. This research used qualitative method the kinds of case study. The result of study shows that Analytic synthesis structure is very relevant to writing skill (maharotul kitabah) which is used in a group of case study in Islamic boarding school of Nurul Jadid. Based on the result of study, it can be concluded that synthesis analysis structure can be Improve writing skill (maharotul kitabah).